O conceito de psicologia em humano, demasiado humano I - REMÍGIO, Luan José Silva (Universidade Federal do Pará, 2017)
The present work aims to explore the concept of psychology as presented in Human, all too human. The formulation of this concept is closely linked to the Nietzschean philosophical project of historical philosophy inaugurated in 1878. This enterprise criticizes the traditional philosophy based on scientific knowledge, which is again valued from the work of 1878. The psychology elaborated by Nietzsche departs from that elaborated by metaphysics, since the philosopher starts from different presuppositions of the tradition when rejecting the body/soul duality and the supremacy of the intelligible over the sensible, when attaching greater importance to the sensitive. Most important, too, is the friendship begun with Paul Rée that will present the French moralists of the seventeenth and eighteenth centuries to the German philosopher. The Duke of La Rochefoucauld, one of these French thinkers, is fundamental for the elaboration of his "psychological observations", as well as the studies on physiology, intensified thereafter. Thus, psychological analysis is necessary to denounce ideals, theoretical, practical and aesthetic as human fictions, too human.